Demonstration of a passive integrated optics technology based on plasmons. - Charbonneau, Robert. (University of Ottawa (Canada), 2001)
The theory surrounding plasmon-polariton wave propagation on infinitely wide thin metal film structures was rederived, understood and is presented. Mode dispersion curves as a function of metal thickness were obtained for various metals and wavelengths. Field distributions for various structures of interest were computed and are presented. Fresnel coefficients have been derived for an n -layer structure to simulate the expected reflectance measurements of attenuated total reflectance (ATR) experiments. ATR experiments have been performed to excite surface plasmon-polaritons on a 20 nm thick titanium (Ti)-gold (Au)-Ti film embedded in SiO2. Measurements of the sensitivity of the thin metal film infinite in width to incident polarisation were performed experimentally confirming the transverse magnetic (TM) nature of surface plasmon-polaritons. A first mask was designed to experimentally verify the optical mode confinement of a thin metal film finite in width. A second mask was designed with the knowledge acquired from the first one. (Abstract shortened by UMI.)
Keywords: Physics, Optics.